A technical, financial and CO2 emission analysis of the implementation of metal foam in a thermal battery for cold chain transport. (March 2021) - Beyne, Wim; Couvreur, Kenny; Lecompte, Steven; De Paepe, Michel
Highlights: Charging time is correlated to the inlet temperature and mass flow rate. The impact of metal foam on charging time depends on the operating point. Metal foam reduces charging time between 24 % and 40 %. Discounted savings up to ten times the original investment cost are possible. Abstract: Latent thermal energy storage (LTES) can be a valuable component in a wide range of energy systems. The low thermal conductivity of most phase change materials (PCMs) has resulted in the development of several PCM enhancement methods. However, most of the comparisons of enhancement techniques implemented in LTES heat exchangers are based on a single operating point which limits the findings to the tested heat transfer fluid inlet temperature and mass flow rate. Furthermore, an analysis of the financial impact of an enhancement method is not available. In this article, the validity of implementing metal foam as a thermal conductivity enhancer is assessed in a cold chain application. A modular LTES design is constructed with and without metal foam. The charging time of both thermal batteries is experimentally correlated as a function of the heat transfer fluid inlet temperature and mass flow rate. The metal foam reduces the charging time of the battery between 24 % and 40 % depending on the heat transfer fluid inlet condition. Discounted savings for the implementation of metal foam of up to 10 times the investment cost are possible but depend on the number of cycles per year and the rate of return.